Long distance movement of DIR1 and investigation of the role of DIR1-like during systemic acquired resistance in Arabidopsis - Champigny, Marc J.; Isaacs, Marisa; Carella, Philip; Faubert, Jennifer; Fobert, Pierre R.; Cameron, Robin K. (Frontiers in Plant Science, 2013)
DIR1 is a lipid transfer protein postulated to complex with and/or chaperone a signal(s) to distant leaves during Systemic Acquired Resistance (SAR) in Arabidopsis. DIR1 was detected in phloem sap-enriched petiole exudates collected from wild-type leaves induced for SAR, suggesting that DIR1 gains access to the phloem for movement from the induced leaf. Occasionally the dir1-1 mutant displayed a partially SAR-competent phenotype and a DIR1-sized band in protein gel blots was detected in dir1-1 exudates suggesting a highly similar protein, DIR1-like (At5g48490), may contribute to SAR. Recombinant protein studies demonstrated that DIR1 polyclonal antibodies recognize DIR1 and DIR1-like. Homology modeling of DIR1-like using the DIR1-phospholipid crystal structure as template, provides clues as to why DIR1-like rarely compensates for the dir1-1 SAR defect. The contribution of DIR1 and DIR1-like during SAR was examined using an Agrobacterium-mediated transient transformation-SAR assay and an estrogen-inducible DIR1-EGFP/dir1-1 line. We provide evidence that upon SAR induction, DIR1 moves down the leaf petiole to distant leaves. Our data also suggests that DIR1-like displays a reduced capacity to move to distant leaves during SAR. The existence of DIR1-like and its infrequent participation in SAR may contribute to the variable SAR responses reported by groups studying SAR mutants.